EMPLOYEE STOCK OWNERSHIP AS STRATEGY TO IMPROVE EMPLOYEE PERFORMANCE (CASE OF BANK SYARIAH MANDIRI YOGYAKARTA) - Chisaan, Aulia Rahmadanti; Zakiy, Muhammad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
The purpose of this study is to analyze the influence of Employee Stock Ownership Program (ESOP) phenomena on employee performance, which can be used as an alternative in conducting a strategic issue by the management of sharia banks and also as an addition to the science horizon through the scientific work that researchers examine. The results of this study can then be arranged as a strategic target related to company resources and competitiveness in increasing competition in the financial industry. This research uses descriptive qualitative research using convenience sampling as a technique of collecting data from a total of 13 informants who are employees of PT Bank Syariah Mandiri Area Yogyakarta and its branch offices with different field positions using interviews as the primary data, with questionnaires and observations as supporting data. The results of this study showed that 31% of informants knew details about the capital market and information about Employee Stock Ownership Program, 61% knew partially, and 8% did not know. The majority of informants (employees) as much as 69% were positively enthusiastic about the enactment of the Employee Stock Ownership Program, and 54% of the total informants expressed interest and wanted to own shares of the company where they worked. The researcher also found data that was of a view and mass perspective as much as 77% Employee Stock Ownership Program had a positive effect on employee performance.Keywords: Bank Syariah Mandiri, Cade Study, Employee Performance, Employee Stock, Strategy